Structural effects on the climatic architecture - Sami, Sania; Zanjany, Roughayeh Rezanejad (Advances in Social Sciences Research Journal, 2018)
climatic architecture, like Islamic architecture and any other traditional architecture, is related to worldview. Traditional Iranian architecture, in a particular way, is an allegory of the universe of existence and human, in its cosmic form. Islamic civilization is a prominent example of a traditional civilization, in which there is the presence of certain extreme principles that shadow the civilization over time and space. Islamic art is nothing more than the reflection of soul in this mundane world. From this perspective, it seems that the definition of sociologists from religious art and Islamic art is different from the sociological definition of art in general [1]. The relationship between architecture and environmental features is important not only for native architects, but also for non-native architects who have grown in a different cultural context. Exploring such an interactive process is full of unique and tricky perceptions, both for non-native architects and for audiences, employers, and analysts. One of the doubts is that in today's world, where the boundaries of countries have lost their credibility in the eyes of architects, and they are always looking for new opportunities in new environments, does this recommendation that the work of architecture should interact with the cultural platform make any sense? The new ideas of globalization, which respect regional attitudes, respond positively to the above question, which ultimately suggests that today, political, social and cultural decisions are made in different parts of the world based on a global-indigenous attitude [2].